Stability analysis of underground excavation - Nguyen, Danh Long. (2010)
This report investigates one of the two basic problems in underground excavation: stress-controlled instability. The report attempts to estimate induced stress, as well as giving insights on and attempting to solve stress-related problems on rock excavations with circular openings. Chapter 3 introduces two methods to analyse boundary stress on a simple circular openings. The first method is using Excel Spreadsheet based on Kirsch’s closed form solution. The second method uses Examine2D and attempt to solve the problems using boundary element method. The two methods would be compared to see their advantages and disadvantages. Chapter 4 researches on probability in rock excavations as well as implementing the First Order Reliability Method (FORM) developed by Low and Tang (2007) to find the reliability index in both normal and non-normal distributions. The results will then be compared to Monte Carlo simulations as done in Hoek (2007). Through all the results obtained, the student can have a better understanding on the different techniques in designing rock tunnels against stress based failures, and an appreciation on the usefulness of probabilistic approach in estimating the probability of failure in rock excavation.